Strategic change in Indian irrigation - Svendsen, Mark; Gulati, Ashok (Macmillan India, 1995)
"Indian Council of Agricultural Research, New Delhi, India; International Food Policy Research Institute, Washington, D.C., U.S.A."; The book contains revised versions of many of the papers presented in the irrigation component of a research workshop held in May 1994 in New Delhi.; Includes bibliographical references (p. [354]-368).; Editors, Mark Svendsen and Asok Gulati.; Partial contents: Sustaining tank irrigation: conjunctive use of tank and well water in Tamil Nadu / K. Palanisami, R. Meinzen-Dick [IFPRI staff], M. Svendsen -- Adequacy and timeliness of irrigation supplies under conjunctive use in the Sone Irrigation System, Bihar / Ruth Meinzen-Dick -- Coping with drought-induced water scarcity in large irrigation systems in Tamil Nadu / L.P. Swaminathan, Ruth Meinzen-Dick -- Evaluating future investment priorities for Tamil Nadu / K. Palanisami, Mark W. Rosegrant [ IFPRI staff].